Sensitivity of Proteus vulgaris to zinc oxide nanoparticles - Sinouvassane Djearamane,; Tharani Ravintharan,; Liang, Sharolynne Xiao Tong; Wong, Ling Shing; Mahadeva Rao U.S.,; Senthilkumar Balasubramanian, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Zinc oxide nanoparticle (ZnO NP) has become a popular choice in nanomedicine and in the treatment of infections. The present study investigated the sensitivity of Proteus vulgaris to ZnO NPs. The bacteriostatic and bactericidal effects on P. vulgaris were determined by using turbidity and colony count methods. The oxidative stress induced by the treatment of ZnO NPs was evaluated by investigating the level of intracellular reactive oxygen species (ROS) along with lipid peroxidation (LP) analysis. The results showed the highest bacterial growth inhibition of 76.21±1.91 and 87.49±3.29% determined using the turbidity and colony count methods, respectively. The highest oxidative stress effects were observed in P. vulgaris exposed to 100 μg/mL of ZnO NPs for 24 h as shown by 510.90±108.53% increase in ROS production and 328.77±44.36% increase in LP level. The Fourier transform infrared spectroscopy (FTIR) spectrum illustrated the possible involvement of functional groups such as amine, alkane, acid and alkene from the bacterial cell wall in allowing the surface attachment of nanoparticles on the bacterial cells. Hence, the present study clearly demonstrated the sensitivity of P. vulgaris to ZnO NPs.